Answer:
(-4, -2)
Explanation:
Rewrite the equations to make y the subject, so that it's easier to calculate the points on each line:
Equation 1
x - y = -2
⇒ x + 2 = y
⇒ y = x + 2
Equation 2
2x - 3y = -2
⇒ 2x + 2 = 3y
⇒ y = (2/3)x + 2/3
Calculate 2 points on each line:
Equation 1 (blue line on attached graph)
Substitute x = 0 and x = -2 into Equation 1 to create 2 points:
x = 0: y = 0 + 2 ⇒ (0, 2)
x = -2: y = -2 + 2 ⇒ (-2, 0)
Plot the points and draw a line through them.
Equation 2 (red line on attached graph)
Substitute x = 2 and x = -1 into Equation 1 to create 2 points:
x = 2: y = (2/3)(2) + 2/3 ⇒ (2, 2)
x = -1: y = (2/3)(-1) + 2/3 ⇒ (-1, 0)
Plot the points and draw a line through them.
Solution
The solution is the point where the two lines intersect.
Therefore, the point of intersection is (-4, -2)